ダイ 24 ジ ナンキョク チイキ カンソク タイ ナツタイ ホウコク 1982-1983 - 大山, 佳邦; オオヤマ, ヨシクニ; Ohyama, Yoshikuni (1984)
P(論文) 第24次観測隊は前 晋爾隊長以下45名(うち夏隊は大山佳邦副隊長以下10名)で構成され, そのほか南極条約に基づく米国人交換科学3名およびオブザーバー2名が同行した。1982年11月25日「ふじ」で東京港を出港した観測隊は, 途中オーストラリアのフリマントル港に寄ったのち, 12月末昭和基地沖の氷海に達した。12月31日昭和基地への第1便を送ったのち, 基地の北西約43km地点に達し, 空輸拠点とした。1983年1月2日から輸送を開始し, 以後好天に恵まれ, 輸送, 基地建設, 野外調査などすべて順調に進み, 1月22日昭和基地への輸送完了, 2月1日予定通り第23次越冬隊と越冬交代を行った。その後, 昭和基地西方約600kmのブライド湾に寄り, 海氷状況, セールロンダーネ山地への接近ルートなどの調査を行ったのち, 海洋観測を実施しながら帰路についた。3月11日ボートルイスに入港し, 第23次越冬隊は下船した。3月17日ポートルイスを出港し, シンガポール経由, 4月20日東京港に帰着した。 This report outlines the summer activities of the 24th Japanese Antarctic Research Expedition (JARE-24) in 1982-1983. The expedition consisted of 35 wintering members led by Dr. Shinji MAE and 10 members of the summer party led by the present author. Three American exchange scientists under the Antarctic Treaty provisions joined the summer party from Tokyo to Fremantle (Dr. T. GOSINK and Mr. T. GREEN) and from Fremantle to Singapore (Mr. G. LANDRETH). The icebreaker FUJI left Tokyo on November 25,1982. After calling at Fremantle, she arrived at the ice edge off Syowa Station on December 31,when the first flight to the station was made. All the cargo for the expedition was transported to the station till January 22,1983 and the wintering members of the JARE-24 took over the duties at the station on February 1. After accomplishment of summer operations in the Syowa Station area, FUJI visited Breid Bay about 600km west of the station. Then she returned to Tokyo on April 20,1983 via Port Louis and Singapore. Oceanographic and ionospheric observations were carried out throughout the voyage. Several field parties for geological, biological and geodetic survey were sent to ice-free areas around Syowa Station. Biological and oceanographical observations under sea ice were carried out at Syowa Station. A party was dispatched to Mizuho Station to take over it and to resupply the materials for wintering. A new power station building at Syowa Station was constructed during the relief period. In the Breid Bay area, the condition of sea ice was observed and some ...